The Incorporation of Citizenship Competency in EFL Learning Materials for Senior High School Students - Fanisa Salma Maida; Ratna Dewanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2021)
This study aims at analysing the extent to which citizenship competency was incorporated and describing ways citizenship competency was incorporated in EFL learning materials for senior high school students. A content analysis was used to analyse 53 EFL learning materials from four public senior high school teachers in East Jakarta. The findings show that citizenship competency is incorporated in most learning materials. Three learning materials did not incorporate citizenship competency, indicated from the none fulfilment of the indicators. However, the indicators were fulfilled in other learning materials. All factors of citizenship competency are incorporated with skills as the highest in incorporation (34.2%), followed by citizenship knowledge (33.6%), attitudes and values (32.2%). Citizenship competency is incorporated through the incorporation of the significant topics, opportunities to apply and develop citizenship skills, and opportunities related to citizenship attitudes and values. Since the types and forms of learning materials are varied, citizenship competency is incorporated in varied ways. These findings are expected to aid teachers in choosing and incorporating citizenship competency in their learning materials.